Chaperone‐mediated autophagy degrades Keap1 and promotes Nrf2‐mediated antioxidative response. Issue 6 (10th May 2022) - Zhu, Lin; He, Shulei; Huang, Lu; Ren, Dongni; Nie, Tiejian; Tao, Kai; Xia, Li; Lu, Fangfang; Mao, Zixu; Yang, Qian
Abstract: Accumulation of oxidative stress is highly intertwined with aging process and contributes to aging‐related diseases, such as neurodegenerative diseases. Deciphering the molecular machinery that regulates oxidative stress is fundamental to further uncovering the pathogenesis of these diseases. Chaperone‐mediated autophagy (CMA), a highly selective lysosome‐dependent degradation process, has been proven to be an important maintainer of cellular homeostasis through multiple mechanisms, one of which is the attenuation of oxidative stress. However, the specific mechanisms underlying this antioxidative action of CMA are not fully understood. In this study, we found that CMA directly degrades Kelch‐like ECH‐associated protein 1 (Keap1), an adaptor of E3 ligase complex that promotes the degradation of nuclear factor erythroid 2‐related factor 2 (Nrf2), which is a master transcriptional regulator in antioxidative response. Activated CMA induced by prolonged oxidative stress led to an increase in Nrf2 level by effectively degrading Keap1, contributing to Nrf2 nuclear translocation and the expression of multiple downstream antioxidative genes. Meanwhile, together with previous study showing that Nrf2 can also transcriptionally regulate LAMP2A, the rate‐limiting factor of CMA process, we reveal a feed‐forward loop between CMA and Nrf2. Our study identifies CMA as a previously unrecognized regulator of Keap1‐Nrf2 pathway and reinforces the antioxidative role of CMA. Abstract : Our findings show that CMA is activated under oxidative condition, resulting in the degradation of Keap1 and activation of Nrf2. This protects cells against oxidative stress. Moreover, Nrf2 increases the transcription of LAMP2A gene, which in turn further activates CMA. We provide a novel mechanism by which CMA‐Nrf2 forms a positive feedback loop to augment antioxidative response and protect cells from oxidative stress.